Employment, Inequality and Globalization: A Continuous Concern - van der Hoeven, Rolph (Cuadernos de Administración, 2010)
This article deals the issue of global economic crisis and its strong impact on the population. Shows concern for the effects of the crisis, mainly through increases in unemployment, which generates greater social inequality as people are forced to work informally, a fact that goes against labor stability and human development. Through a look at the position assumed by several authors who handle financial issues, is that public policies arising from different periods have not been a satisfactory answer to balance socioeconomic inequalities because it has not been possible to achieve economic growth result in a more equitable income distribution, capable of generate a true human development. Alternatives are contemplated to promote employment growth, from fiscal and monetary toward the industrial and commercial, as are some positions to face the effects of globalization.